Compact workstation from Kelempayan (Neolamarckia cadamba) / Nur Hannani Abdul Latif ... [et al.] - Abdul Latif, Nur Hannani; Kamarudin, Norashikin; Ahmad Zaki, Junaiza; Shafie, Amran; Zakaria, Shaikh Abdul Karim Yamani; Othman, Ahmad Fauzi; Abdullah, Azuandi (2015)
Furniture is a necessity that has become a trend in accordance with the latest technology and development. There are high demands for multifunctional furniture that can fit into small space, especially for consumers staying in small houses, apartments or hostels. The objective of this study was to design a space saving, multifunctional compact workstation from Kelempayan (Neolamarckia cadamba). At the end of the design and manufacturing phases, a survey was taken to evaluate the characteristics of the product. A set of questionnaires were distributed to 100 correspondents of University Teknologi (UiTM) based on gender, profession and range of age. The characteristics evaluated were suitability of material, compact concept, design, portability, comfortability, spacing, multifunction, commercialization and price of product. Results showed that gender factor influenced the evaluation on the characteristics of the product, but there was no significant difference on the evaluation based on the profession and range of age. It can be concluded that Kelempayan (Neolamarckia cadamba) is a suitable material to produce this compact workstation. This compact workstation has proven to be multifunctional, suitable for limited space and has great potential to be commercialized in the furniture industry of Malaysia.